The peculiarity of advertisement language (Eurasian Journal of Philology Science and Education, 2015)
The language was the first problem when Kazakhstan took independence. One of the important thing was the advertisement language.This article is talking about interpreting of advertisement language and also about thecommunicative peculiarity pragmatic fundaments is not only economical object but also the main sphere of linguistics. Тhere are a lot of examples in order to show the peculiarities of advertisement language. The articleconsists of a lot of exact facts about advertisement language. Nowadays one of the researching problems is the culture of advertisement language. In order to know advertisement we should understand the advertisement language.
Keywords: the advertisement interpreting; the aspect of communication; practical fundament; language peculiarity and cognition.